Certified Organic Intellectual: On Not Being Postmodern: Aurora Levins Morales - Echazú Böschemeier , Ana Gretel; Giatti Carneiro, Rosamaria (Revista de Estudos e Pesquisas sobre as Américas, 2021)
Text authorized by the author and publisher from the book Medicine Stories: Essays for Radicals. Year of publication: 2019. Pages: 121-126. Duke University Press. An earlier version of this essay was published in Medicine Stories, 1998, South End Press.